Beraprost Sodium, a Stable Analogue of PGI2, Inhibits the Renin-Angiotensin System in the Renal Tissues of Rats with Chronic Renal Failure - Xin-Fang Wang; Bei-Hao Zhang; Xiao-Qing Lu; Pei Wang (Karger Publishers, 2018)
Background/Aims: Chronic renal failure (CRF) is a prolonged kidney condition characterized by decreased kidney function that can eventually develop into total kidney failure. The renin-angiotensin system (RAS) helps to regulate the balance between human bodily fluids and electrolytes. The aim of the present study was to investigate the effects of a prostacyclin analogue (beraprost sodium [BPS]) on the expression of key factors associated with local RAS activities in the renal tissues of rats with CRF. Methods: After a CRF rat model was successfully established, the levels of BUN, SCr, phosphorus, and calcium were detected by an automatic biochemistry analyzer. Furthermore, the activities of malondialdehyde (MDA) and superoxide dismutase (SOD) in rat renal tissues were measured using a colorimetric method, while the activity of angiotensin-converting enzyme (ACE) was determined by ultraviolet (UV) spectrophotometry. In situ hybridization was employed to determine the expression of angiotensin II type 1 receptor (AT). Finally, the positive expression rates of cells expressing important apoptotic proteins (Bax and Bcl-2) were determined, and the protein and mRNA levels of phosphatidylinositol 3-kinase (AKT) and key factors involved in the RAS (AT1, AT2, angiotensin ACE and angiotensinogen [AGT]) were evaluated by RT-qPCR and western blot analysis. Results: Initial observations revealed that treatment with BPS decreased the levels of BUN, SCr and phosphorus but increased calcium levels in the renal tissues of CRF rats. Additionally, BPS reduced the levels of MDA while increasing the levels of SOD, ACE activity, and AT1 expression in the renal tissues of CRF rats. BPS inhibited glomerular hypertension and hyperfiltration; increased the mRNA and protein levels of AKT and AT2; and decreased the mRNA and protein levels of AT1, AGT, and ACE in the renal tissues of CRF rats. Conclusion: The results of this study demonstrate that BPS, a PGI2 analogue, inhibits the expression of key factors involved in the local RAS, resulting in a delay in the occurrence and development of CRF. The key findings of the present study ultimately highlight the potential of this PGI2 analogue as a promising therapeutic strategy for treating CRF.